Islam-based peace education: values, program, reflection and implication - M Abdul Fattah Santoso; Yayah Khisbiyah (IAIN Salatiga, 2021)
There is a gap between ideal Islam and real Islam. Ideal Islam means peace, greeting, safety, salvation, and conceptually means absolute submission to God`s Will. Real Islam resembles unresolved conflicts in some communities and unpleasant meanings to some non-Muslims. To minimize the gap, it is important to socialize peaceful Islamic values in the community through education. This study aims to explain Pendidikan Perdamaian Berbasis Islam (PPBI, the Islam-based Peace Education) program initiated by Pusat Studi Budaya dan Perubahan Sosial (PSB-PS, the Center for the Study of Culture and Social Change) at Universitas Muhammadiyah Surakarta (UMS). This participatory action research is especially to reveal Islamic values identified in the PPBI program in terms of its uniqueness, implementation, reflection, and implication. Based on the Sirah of the Prophet and the Al-Qur’an, the PPBI program has identified 15 Islamic values which contribute to peacebuilding. Those values were used as core contents of PPBI’s handbook and classroom program. The program has been implemented through series of activities ranging from seminars, FGDs, workshops, training of teachers, publication of books, and classroom implementation. PPBI program based on nonviolence and peacebuilding assumptions, i.e. to build a culture of peace, is designed as the formal peace education through learning materials and classroom processes either in any existing course or co-curricular activities.